Case report: Outer lamellar macular hole and outer retinal detachment within myopic foveoschisis post-cataract surgery - Eng, Yii Hern; Ong, Kah Wei; Yong, Meng Hsien; Wan Abdul Halim, Wan Haslina; Bastion, Mae-Lynn Catherine (Frontiers in Medicine, 2023)
Background This study aimed to report a case of outer lamellar macular hole and outer retinal detachment within myopic foveoschisis (MF) post-cataract surgery. Case presentation An elderly female patient with bilateral high myopia and pre-existing myopic foveoschisis underwent uncomplicated sequential cataract surgeries 2 weeks apart. She was able to achieve a satisfactory visual outcome for her left eye with stable myopic foveoschisis and visual acuity of 6/7.5, near vision N6. However, her right eye vision remained poor postoperatively, with a visual acuity of 6/60. Macular optical coherence tomography (OCT) revealed a new right eye outer lamellar macular hole (OLMH) and outer retinal detachment (ORD) within pre-existing myopic foveoschisis. Her vision remained poor after 3 weeks of conservative management, and she was offered vitreoretinal surgical intervention with pars plana vitrectomy, internal limiting membrane peeling, and gas tamponade. However, she refused surgical intervention, and her right vision remained stable at 6/60 over 3 months of follow-up. Conclusion Outer lamellar macular hole and outer retinal detachment within myopic foveoschisis can occur soon after cataract surgery, which may be related to the progression of associated vitreomacular traction, and have a poor visual outcome if left untreated. Patients with high myopia should be informed of these complications as part of pre-operative counseling.